2013
DOI: 10.1002/nau.22433
|View full text |Cite
|
Sign up to set email alerts
|

Safety and one year outcomes following vaginally assisted laparoscopic uterine sacropexy (VALUES) for advanced uterine prolapse

Abstract: VALUES is a safe and effective treatment for women with stage 3 and 4 uterine prolapse up to 12 months without the risk of vaginal shortening. Long-term results are needed to fully establish the value of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…Various techniques have been described for the treatment of uterine prolapse using vaginal, abdominal, or laparoscopic approaches . Maher et al reported a 74% objective success rate of sacrospinous hysteropexy, which compared favourably to vaginal hysterectomy with concomitant sacrospinous fixation of the vault in a retrospective series of 70 women …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various techniques have been described for the treatment of uterine prolapse using vaginal, abdominal, or laparoscopic approaches . Maher et al reported a 74% objective success rate of sacrospinous hysteropexy, which compared favourably to vaginal hysterectomy with concomitant sacrospinous fixation of the vault in a retrospective series of 70 women …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally vaginal hysterectomy has been widely popular among gynaecologists for the treatment of uterovaginal prolapse; however, associated with reported variable high recurrence rate (11.6–40%) . This has led to the approach being challenged as often hysterectomy results in removal of a normal organ, regarded as having a passive role in the prolapse process, where the pathology lies in the suspension of the uterus rather than the uterus itself …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current surgical techniques include sacropexy, pectopexy, laparoscopic ligament suspension (LLS), and laparoscopic uterosacral ligament suspension (LUSLS). Modifications using the vaginal approach are also used, for example vaginally‐assisted laparoscopic uterine sacrocolpopexy …”
Section: Introductionmentioning
confidence: 99%